Analisis Biaya Relevan untuk Pengambilan Keputusan Menerima atau Menolak Pesanan Khusus pada CV. Prek Jhon - Mustafiyatus Nur Lailina; Hwihanus Hwihanus (Pusat Riset dan Inovasi Nasional, 2025)
Mustafiyatus Nur Lailina, 2024. Relevant Cost Analysis for Decision Making to Accept or Reject Special Orders at CV. Prek John. Supervised by Dr. Hwihanus. S.E., M.M., C.M.A. This research aims to find out how to analyze relevant costs in making decisions to accept or reject special orders on CV. Prek John. The problem is the extent to which relevant cost analysis plays a role in management decision making to accept or reject special orders. The research object is CV. Prek Jhon whose address is Jalan Wunut Porong. This research uses quantitative descriptive methods using interviews, observation and data analysis as sources. With a research approach, understanding cost analysis is relevant in making decisions to accept or reject special orders. The research results show that in determining orders using relevant costs using the variable costing method, a profit of IDR 5,480,000 is obtained by eliminating the fixed element, namely equipment maintenance costs. So, a special order of 2,000 boxes of Crispy Jhon 2 using variable costing is better accepted.